Peran Orang Tua dalam Implementasi Program LKKNU untuk Mencegah Pernikahan Dini di Sumenep - AS, Rozinah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2024)
The Nahdlatul Ulama Family Benefits Institute (LKKNU) program has a role in prevention efforts through counseling and assistance to the community. However, the role of parents in implementing this program still needs to be explored in more depth. This research aims to analyze the role of parents in supporting the implementation of the LKKNU program to prevent early marriage in Sumenep. The problem formulation in this research is: What is the role of parents in participating and supporting the LKKNU program? What are the factors that influence the success of parents' role in preventing early marriage through the LKKNU program? The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews with parents involved in the LKKNU program, as well as observations of the activities held. The theories used are community participation theory and social change theory, which explains how parental involvement can influence social change in preventing early marriage. The research results show that the role of parents is very significant in the success of the LKKNU program. Their support in terms of active participation and providing information to their children has succeeded in reducing the rate of early marriage in Sumenep. This research also recommends the need to increase education to parents about the importance of the program.